Pengaruh Rasio Crude Enzim Aspergillus niger dan Trichoderma reesei terhadap Kadar Gula dan Bioetanol Hasil Fermentasi Kulit Buah Nangka (Artocarpus heterophyllus Lamk.) - Pertiwi, Diana; Widyaningrum, Trianik (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022)DO - 10.24843/metamorfosa.2022.v09.i02.p18, 2022)
Bioethanol is ethanol derived from biological sources and can be used as an alternative fuel. Bioethanol can be made from materials that contain cellulose, for example jackfruit rind which contains 38.69% cellulose. The purpose of this study was to determine the effect of the ratio of crude enzymes Aspergillus niger and Trichoderma reesei to the sugar and bioethanol content of fermented jackfruit rind using Zymomonas mobilis . This type of research is experimental research. The experimental design used RAL with the independent variable ratio of crude Aspergillus niger and Trichoderma reesei with variants (0:0), (0:1), (1:0), (1:1), (1:2), (2:1 ), (1:3), and (3:1). The dependent variables were sugar content and bioethanol from fermented jackfruit rind. Sugar content was measured by the DNS method. Ethanol content was measured using an alcoholmeter. Experimental data were analyzed by ANOVA. The results showed that the ratio of crude enzymes Aspergillus niger and T richoderma reesei affected the sugar content and bioethanol fermented jackfruit peel using Zymomonas mobilis . The highest sugar content in the crude enzyme ratio Aspergillus niger : Trichoderma reesei 1:0 of ??11.99% and the highest ethanol content of the crude ratio of 2: 1, which is 3.16%.